Dependence of the dielectric properties of suspensions on the volume fraction of suspended particles - Grosse, Constantino (2007)
It is shown that the fundamental expression for the complex permittivity of a dilute suspension of monodispersed, spherical particles, where is the complex permittivity of the suspending medium and the dipolar coefficient, is strictly valid for any value of the volume fraction ϕ of particles in the suspension, provided that is interpreted as the ensemble average value of the dipolar coefficient of the particles and is defined in terms of the macroscopic electric field in the suspension. Graphical abstract The fundamental expression for the complex permittivity of a dilute suspension of particles in a suspending medium : is strictly valid for any value of the volume fraction ϕ, provided that the dipolar coefficient is interpreted as the ensemble average value of the particles and is defined in terms of the macroscopic electric field in the suspension.